2016
DOI: 10.1590/1983-21252016v29n429rc
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION AND EFFECTS OF MIXED INFECTION OF Potyvirus ISOLATES WITH Cucumber mosaic virus IN CUCURBITS

Abstract: -Mixed infections in cucurbits are frequently observed in natural conditions between viruses from the Potyvirus genus and Cucumber mosaic virus (CMV), which significantly decreases productivity. The objectives of the present study was to compare the host range of PRSV-W, WMV, and ZYMV isolates and evaluate the effects of mixed infections with CMV in zucchini plants (Cucurbita pepo L.). Host range studies comprising 23 plant species confirmed some similarities and biological differences among the isolates of PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
2
8
0
1
Order By: Relevance
“…In Oklahoma, 18.9% of samples were found to be infected with at least two viruses among 869 cucurbit samples [ 6 ]. A high incidence of mixed infections involving PRSV-W, WMV, and ZYMV has also been reported previously in different studies around the world: in the USA [ 6 , 20 , 22 ], Iran [ 12 ], Spain [ 13 ], Brazil [ 42 ], Panama [ 14 ], Venezuela [ 43 ], South Africa [ 44 ], Ivory Coast [ 45 ], Argentina [ 18 ], India [ 16 ], and France [ 19 ]. However, the proportion of mixed infections involving these three viruses in this study was higher than that in previous studies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In Oklahoma, 18.9% of samples were found to be infected with at least two viruses among 869 cucurbit samples [ 6 ]. A high incidence of mixed infections involving PRSV-W, WMV, and ZYMV has also been reported previously in different studies around the world: in the USA [ 6 , 20 , 22 ], Iran [ 12 ], Spain [ 13 ], Brazil [ 42 ], Panama [ 14 ], Venezuela [ 43 ], South Africa [ 44 ], Ivory Coast [ 45 ], Argentina [ 18 ], India [ 16 ], and France [ 19 ]. However, the proportion of mixed infections involving these three viruses in this study was higher than that in previous studies.…”
Section: Discussionsupporting
confidence: 74%
“…They may also lead to virus–virus interactions within a host, resulting in new variants with novel features [ 47 ]. Mixed virus infections can be antagonistic [ 47 , 48 , 49 , 50 ], synergistic [ 42 , 51 , 52 , 53 ], or neutral [ 53 , 54 ]. Additionally, the suppression of post-transcriptional expression by one virus helps in the replication of another virus, thereby forming a synergistic association [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar phenomenon was also reported by Barbosa et al (2016) in Brazil, in which mixed infection of CMV, WMV, ZYMV and PRSV on cucurbits showed a variety of symptoms in the field. In Java and Central Java, there have also been reported mix infections of viruses in Cucurbits.…”
Section: Presence Of CMV In Sample Crops Based On Tas Elisasupporting
confidence: 87%
“…The second possibility is that the crops were infected by other distinct cucurbits viruses. Many authors reported that cucurbits could be infected by many viruses, commonly CMV, PRSV, ZYMV, WMV and others both in single or mix infection that induce a variety of symptoms including symptoms of CMV infection such as mosaic, vein clearing, vein banding and malformation (Zitter and Murphy, 2009;Romay et al, 2014;Barbosa et al, 2016;Sydanmetsa and Mbanzibwa, 2016).…”
Section: Presence Of CMV In Sample Crops Based On Tas Elisamentioning
confidence: 99%
“…The fruits are stunted and deformed, resulting in reduced yield and making them non-marketable (Spadotti et al, 2015). ZYMV is markedly present in the producing regions of Brazil; Barbosa et al (2016), in a survey in the Vale do Rio São Francisco, obtained 44% symptomatic plants with the presence of this virus.…”
mentioning
confidence: 99%